Poly(ADP-ribose) polymerase-1 promotes expression of miR-155 by the up-regulation of methyl-CpG binding domain protein 2 in TK6 cells exposed to hydroquinone. (March 2019) - Gui, Zhiming; Zhang, Haiqiao; Tan, Qiang; Ling, Xiaoxuan; Liu, Zhidong; Peng, Jianming; Shao, Junli; Wu, Minhua; Yuan, Qian; Li, Jieyou; Pan, Zhijie; Zhong, Baisen; et al.
Abstract: Hydroquinone (HQ), one of the major metabolites of benzene, can induce aberrant gene expression. MiR-155, a tumor activator, participates in various biological processes, including DNA damage response. However, the molecular mechanism of aberrant miR-155 expression is still not completely elucidated. Here, we investigated the mechanism of abnormal expression of miR-155 induced by poly(ADP-ribose)polymerase-1 (PARP-1) expression in HQ-treated TK6 lymphoblastoid cells. We examined the expression of genes related to abnormal expression of miR-155 to explore the reason for this phenomenon. The results of the present study showed that miR-155 was significantly increased and reactive oxygen species (ROS) were decreased in cells treated with HQ for 72 h compared with PBS-treated cells. Meanwhile, E4F1, PARP-1 and PARP-1 related co-regulators (NF-κB, HDAC1, and HDAC2), acetylated histone H3 (H3Ac) were increased in a concentration-dependent manner. Experiments for treatment with 5-AzaC (DNMTs inhibitor), TSA (HDACs inhibitor), DOX (to activate PARP-1) or MG132 (proteasome inhibitor) revealed that the MBDs and PARP-1 was positively associated with miR-155 expression. Moreover, in cells treated with HQ in conjunction with PARP-1 knockdown, expression of miR-155, H3Ac and MBD2 protein were decreased, compared with negative control. In conclusion, PARP-1 activates expression of miR-155 via acetylation by regulating MBD2 in TK6 cells exposed to HQ. Highlights: HQ activates the expression of miR-155 and PARP-1 in a dose-dependent manner. HQ induces the expression of PARP-1 related co-regualtors (HDAC1/2, NF-κB, ). Treatment of TSA and DOX promotes the expression of miR-155. PARP-1 silencing inhibits the expression of miR-155 and MBD2. PARP-1 promotes the expression of miR-155 via histone acetylation by targeting MBD2.